Negative pole piece, secondary battery and electronic device
By using silicon oxide or silicon carbide as the first negative electrode active material and lithium lanthanum zirconium oxide as fast ion conductors in the negative electrode sheet of the lithium-ion battery, the problem of easy expansion of the negative electrode material is solved, and the expansion and cycle stability of the secondary battery are improved.
Patent Information
- Application Number
- CN202311163532.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
AI Technical Summary
The negative electrode material of lithium-ion batteries is prone to expansion, resulting in poor gas production and circulation performance of secondary batteries, limiting their large-scale applications.
A negative electrode sheet structure is adopted, wherein the negative electrode material layer includes silicon oxide or silicon carbide as the first negative electrode active material, and lithium lanthanum zirconium oxide is used as the fast ion conductor. The fast ion conductor is distributed on the surface of the first negative electrode active material, and a solid-state electrolyte film is formed to improve battery performance by regulating the particle size and proportion of the material.
It effectively improves the expansion problems and cycle stability of the secondary battery, and improves the mechanical and electrochemical properties of the negative electrode sheet.
Smart Images

Figure CN119601583A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a negative electrode sheet, a secondary battery and an electronic device. Background Art
[0002] Secondary batteries such as lithium-ion batteries are widely used in all aspects of life today due to their advantages such as no memory effect, small size, light weight, and environmental protection. In recent years, secondary batteries have been rapidly developed in the fields of new energy vehicles and energy storage.
[0003] However, when the negative electrode material of the lithium-ion battery is a carbon-based material such as graphite, its capacity is low, resulting in low energy density; and when the negative electrode material of the lithium-ion battery is a silicon-based material, since the silicon-based material is easy to expand, the secondary battery is prone to expansion and gas production, and the cycle performance is poor, which greatly limits their large-scale application in lithium-ion batteries. Summary of the invention
[0004] The purpose of this application is to provide a negative electrode plate, a secondary battery and an electronic device to improve the expansion and cycle stability of the secondary battery. The specific technical solution is as follows:
[0005] The first aspect of the present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector, the negative electrode material layer includes a negative electrode active material and a fast ion conductor, the negative electrode active material includes a first negative electrode active material, at least part of the fast ion conductor is arranged on the surface of the first negative electrode active material, the first negative electrode active material includes at least one of silicon monoxide (SiOx, x = 1 ± 0.2) or silicon carbide, and the fast ion conductor is lithium lanthanum zirconium oxide; the Dv50 of the first negative electrode active material is D1μm, the Dv50 of the fast ion conductor is D2μm, D2 / D1≤0.2, preferably, 0.01≤D2 / D1≤0.14, and 0.05≤D2≤1, preferably, 0.3≤D2≤0.7. By regulating the types of the first negative electrode active material and the fast ion conductor, at least part of the fast ion conductor is disposed on the surface of the first negative electrode active material, and the values of D2 / D1 and D2 are within the scope of this application, the gas production of the secondary battery can be improved, and the deformation of the pole piece caused by the volume expansion of the negative electrode active material during the charge and discharge process can also be improved, thereby improving the overall expansion of the secondary battery. On the other hand, since the particle size of the added fast ion conductor is small and the fast ion conductor is a ceramic material, the ceramic material has strong rigidity and can improve the mechanical properties of the negative electrode pole piece, thereby improving the problem of poor electrical performance including cycle stability caused by deformation or breakage of the first negative electrode active material.
[0006] In one embodiment of the present application, 5≤D1≤15. By adjusting the value of D1 within the scope of the present application, the particle size of the first negative electrode active material can be better matched with the particle size of the fast ion conductor, so that the fast ion conductor forms a more stable solid-state electrolyte membrane together with the solid electrolyte layer (SEI layer) generated during the formation process on the surface of the first negative electrode active material, further improving the expansion and cycle stability of the secondary battery.
[0007] In one embodiment of the present application, the Dv99 of the fast ion conductor is D3 μm, 0.1≤D2 / D3<1, preferably, 0.5≤D2 / D3<1. By adjusting the value of D2 / D3 within the scope of the present application, the fast ion conductor can have a suitable particle size distribution, the solid-state electrolyte film on the surface of the first negative electrode active material can be more uniform, and the expansion and cycle stability of the secondary battery can be further improved.
[0008] In one embodiment of the present application, 0.5≤D3≤5. By adjusting the value of D3 within the scope of the present application, the processing cost of the fast ion conductor can be reduced while ensuring the uniformity of the fast ion conductor particles, and the particle size of the fast ion conductor can be better matched with the particle size of the negative electrode active material, thereby further improving the expansion, storage performance and cycle stability of the secondary battery.
[0009] In one embodiment of the present application, the ionic conductivity of the fast ion conductor is 1.44×10 -5 S / m to 1.09×10 -3 By controlling the ionic conductivity of the fast ion conductor within the scope of the present application, the conductivity of the negative electrode active material can be increased, which helps to further improve the cycle stability of the secondary battery.
[0010] In one embodiment of the present application, the fast ion conductor has a molecular formula of any one of formula (A), formula (B) or formula (C):
[0011] Li α M β La3Zr2O 12 (A)
[0012] In formula (A), M includes at least one of Ga, Al or Fe, satisfying: α+3β=7, α≥5.5, β≥0;
[0013] 7La γ R δ Zr2O 12 (B)
[0014] In formula (B), R is at least one of Ce or Y, satisfying: 3γ+3δ=9, γ≥2.5, δ≥0;
[0015] Li7La3Zr a X b Q c O 12 (C)
[0016] In formula (C), X and Q are each independently selected from at least one of Ta, Nb, Sn, Sb, W, Te, Cr or Y, satisfying: a+b+c=2, a≥1, b≥0, c≥0. By selecting the above fast ion conductor, the electrochemical window of the undoped fast ion conductor can be expanded, the electrochemical stability of the fast ion conductor can be increased, and it can serve as a more stable and efficient transition layer for conducting lithium ions, which is conducive to further improving the cycle stability of the secondary battery.
[0017] In one embodiment of the present application, the fast ion conductor comprises Li7La3Zr2O 12 , Li 6.28 Al 0.24 La3Zr2O 12 , Li 6.25 Ga 0.25 La3Zr2O 12 , Li 6.4 Ga 0.2 La3Zr2O 12 、Li7La 2.5 Ce 0.5 Zr2O 12 、Li7La 2.875 Y 0.125 Zr2O 12 or Li7La3ZrNb 0.5 Y 0.5 O 12 By selecting the above-mentioned fast ion conductor, a solid-state electrolyte membrane can be formed on the surface of the first negative electrode active material, which can provide a lithium ion diffusion channel and inhibit the side reaction between the first negative electrode active material and the electrolyte, protect the first negative electrode active material, improve the gas production of the secondary battery, and improve the cycle stability of the secondary battery.
[0018] In one embodiment of the present application, the negative electrode material layer further includes a binder and a conductive agent. Based on the total mass of the negative electrode material layer, the mass percentage of the negative electrode active material is 80% to 98%, the mass percentage of the fast ion conductor is 0.1% to 16%, and the sum of the mass percentages of the binder and the conductive agent is 1% to 4%. By regulating the mass percentages of the negative electrode active material and the fast ion conductor within the scope of the present application, the secondary battery has a higher energy density while the fast ion conductor has an improved ability to protect the interface, thereby improving the gas production of the secondary battery and improving the cycle stability of the secondary battery.
[0019] In one embodiment of the present application, the negative electrode active material further includes a second negative electrode active material, the second negative electrode active material includes at least one of artificial graphite or natural graphite, and based on the total mass of the negative electrode active material, the mass percentage of the first negative electrode active material is 2% to 20%, preferably, the mass percentage of the first negative electrode active material is 6% to 13%. When the negative electrode active material further includes the second negative electrode active material, by adjusting the mass percentage of the first negative electrode active material to the negative electrode active material within the scope of the present application, the secondary battery has a higher energy density, and the secondary battery has less expansion and improved cycle stability.
[0020] The second aspect of the present application provides a secondary battery, which includes the negative electrode sheet in any of the above embodiments. Therefore, the secondary battery provided by the present application is not easy to expand and has good cycle stability.
[0021] The third aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.
[0022] Beneficial effects of this application:
[0023] The present application provides a negative electrode plate, a secondary battery and an electronic device, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer comprises a negative electrode active material and a fast ion conductor, the negative electrode active material comprises a first negative electrode active material, at least part of the fast ion conductor is disposed on the surface of the first negative electrode active material, the first negative electrode active material comprises at least one of silicon oxide or silicon carbide, and the fast ion conductor is lithium lanthanum zirconium oxide; the Dv50 of the first negative electrode active material is D1 μm, the Dv50 of the fast ion conductor is D2 μm, D2 / D1≤0.2, and 0.05≤D2≤1. By regulating the types of the first negative electrode active material and the fast ion conductor, at least part of the fast ion conductor is disposed on the surface of the first negative electrode active material, and the values of D2 / D1 and D2 are within the scope of the present application, the expansion and cycle stability of the secondary battery can be improved.
[0024] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0026] Figure 1 This is a schematic diagram of a structure in which a fast ion conductor is distributed on the surface of a first negative electrode active material in one embodiment of the present application;
[0027] Figure 2 This is a cross-sectional scanning electron microscope image of the negative electrode sheet of Example 1-1 of the present application. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0029] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0030] The present application provides a negative electrode sheet, which includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer includes a negative electrode active material and a fast ion conductor, wherein the negative electrode active material includes a first negative electrode active material, and at least part of the fast ion conductor is disposed on the surface of the first negative electrode active material, such as Figure 1 As shown, the fast ion conductor 2 is distributed on the surface of the first negative electrode active material 1. The first negative electrode active material includes at least one of silicon monoxide (SiOx, x=1±0.2) or silicon carbide, and the fast ion conductor is lithium lanthanum zirconium oxide.
[0031] The Dv50 of the first negative electrode active material is D1 μm, the Dv50 of the fast ion conductor is D2 μm, D2 / D1≤0.2, preferably, 0.01≤D2 / D1≤0.14, and illustratively, D2 / D1 can be 0.001, 0.003, 0.005, 0.007, 0.009, 0.01, 0.013, 0.015, 0.017, 0.019, 0.02, 0.023, 0.025, 0.027, 0.029, 0.03, 0.033, 0.035, 0.037, 0.039, 0.04, 0.043, 0.045, 0.047, 0.049, 0.05, 0.053, 0.055, 0.057, 0.059, 0.06, 0.063, 0.065, 0.067, 0.069, 0.07, 0.073, 0.075, 0.077, 0.079, 0.08, 0.083, 0.085, 0.087, 0.089, 0.09, 0.093, 0.095, 0.097, 0.099, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, or a range consisting of any two of the above values. And 0.05≤D2≤1, preferably, 0.3≤D2≤0.7, illustratively, D2 can be 0.05, 0.07, 0.09, 0.1, 0.13, 0.15, 0.17, 0.19, 0.2, 0.23, 0.25, 0.27, 0.29, 0.3, 0.33, 0.35, 0.37, 0.39, 0.4, 0.43, 0.45, 0.47 , 0.49, 0.5, 0.53, 0.55, 0.57, 0.59, 0.6, 0.63, 0.65, 0.67, 0.69, 0.7, 0.73, 0.75, 0.77, 0.79, 0.8, 0.83, 0.85, 0.87, 0.89, 0.9, 0.93, 0.95, 0.97, 0.99, 1 or a range consisting of any two of the above values.
[0032] The inventors have found that the negative electrode material layer includes the above-mentioned negative electrode active material and the fast ion conductor. On the one hand, the fast ion conductor can be attached to the surface of the first negative electrode active material to form a solid-state electrolyte membrane, improve the fast ion conductor's ability to protect the interface and the conductivity of the negative electrode active material, inhibit the gas production of the secondary battery, and the addition of the fast ion conductor can also absorb the gas production of the secondary battery, thereby improving the gas production of the secondary battery. On the other hand, it can also improve the deformation of the pole piece caused by the volume expansion of the negative electrode active material during the charge and discharge process, thereby improving the overall expansion of the secondary battery. On the other hand, since the added fast ion conductor has a small particle size, the fast ion conductor can form a solid-state electrolyte membrane on the surface of the first negative electrode active material, making the first negative electrode active material more stable; and the fast ion conductor is a ceramic material, and the ceramic material has strong rigidity, which can inhibit the volume change of the first negative electrode active material, thereby improving the mechanical properties of the negative electrode pole piece, and then improving the problem of poor electrical performance including cycle stability caused by deformation or breakage of the first negative electrode active material. At the same time, when the value of D2 / D1 is too large (for example, greater than 0.2), the effect of fast ion conductor adhering to the surface of the first negative electrode active material will be poor, the improvement of gas production of the secondary battery will be limited, and it will not be conducive to the improvement of cycle stability. When the value of D2 is too large (for example, greater than 1), the surface of the first negative electrode active material will be less covered, the interface protection will not be good enough, the improvement of gas production of the secondary battery will be limited, and it will not be conducive to the improvement of cycle stability; when the value of D2 is too small (for example, less than 0.05), the production technology and production cost are required to be high, which affects the actual use. Therefore, when the types of the first negative electrode active material and the fast ion conductor, at least part of the fast ion conductor is arranged on the surface of the first negative electrode active material, and the values of D2 / D1 and D2 are within the scope of this application, the expansion and cycle stability of the secondary battery can be improved.
[0033] In the present application, "at least part of the fast ion conductor is arranged on the surface of the first negative electrode active material" means that the first negative electrode active material can have a fast ion conductor on part of the surface or on the entire surface. This application has no special restrictions as long as the purpose of this application can be achieved.
[0034] In the present application, Dv50 refers to the particle size at which the volume accumulation is 50% measured from the smallest particle size in the volume-based particle size distribution of the material.
[0035] In one embodiment of the present application, 5≤D1≤15. Exemplarily, D1 can be 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15 or a range consisting of any two of the above values. By regulating the value of D1 within the scope of the present application, the particle size of the first negative electrode active material can be better matched with the particle size of the fast ion conductor, so that the fast ion conductor forms a more stable solid-state electrolyte membrane on the surface of the first negative electrode active material and the solid electrolyte layer (SEI layer) generated during the formation process, further improving the expansion and cycle stability of the secondary battery.
[0036] In one embodiment of the present application, the Dv99 of the fast ion conductor is D3 μm, 0.1≤D2 / D3<1, preferably, 0.5≤D2 / D3<1, and illustratively, D2 / D3 can be 0.1, 0.13, 0.15, 0.17, 0.19, 0.2, 0.23, 0.25, 0.27, 0.29, 0.3, 0.33, 0.35, 0.37, 0.39, 0.4, 0.43 , 0.45, 0.47, 0.49, 0.5, 0.53, 0.55, 0.57, 0.59, 0.6, 0.63, 0.65, 0.67, 0.69, 0.7, 0.73, 0.75, 0.77, 0.79, 0.8, 0.83, 0.85, 0.87, 0.89, 0.9, 0.93, 0.95, 0.97, 0.99 or a range consisting of any two of the above values. By regulating the value of D2 / D3 within the scope of this application, the fast ion conductor can have a suitable particle size distribution, the solid-state electrolyte film on the surface of the first negative electrode active material can be more uniform, and the expansion and cycle stability of the secondary battery can be further improved.
[0037] In the present application, Dv99 refers to the particle size reaching 99% of the volume accumulation measured from the smallest particle size in the volume-based particle size distribution of the material.
[0038] In one embodiment of the present application, 0.5≤D3≤5. Exemplarily, D3 can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of the above values. By regulating the value of D3 within the scope of the present application, the processing cost of the fast ion conductor can be reduced while ensuring the uniformity of the fast ion conductor particles, and the particle size of the fast ion conductor can be better matched with the particle size of the first negative electrode active material, thereby further improving the expansion, storage performance and cycle stability of the secondary battery.
[0039] The present application has no particular restrictions on the method of regulating the Dv50 and Dv99 of the above-mentioned fast ion conductors, as long as the purpose of the present application can be achieved. Exemplarily, the Dv50 and Dv99 of the fast ion conductor can be regulated by grinding the fast ion conductor. For example, the Dv50 of the above-mentioned fast ion conductor can be regulated by regulating the grinding time and the grinding speed; the Dv99 of the above-mentioned fast ion conductor can be regulated by regulating the grinding time and the grinding speed. Exemplarily, when other conditions remain unchanged, the Dv50 of the fast ion conductor decreases and the Dv99 of the fast ion conductor decreases by extending the grinding time; the Dv50 of the fast ion conductor increases and the Dv99 of the fast ion conductor increases by shortening the grinding time.
[0040] The present application has no particular restrictions on the method for regulating the Dv50 of the first negative electrode active material, as long as the purpose of the present application can be achieved. Exemplarily, the Dv50 of the first negative electrode active material can be regulated by grinding the first negative electrode active material. For example, the Dv50 of the first negative electrode active material can be regulated by regulating the grinding time and the grinding speed. Exemplarily, when other conditions remain unchanged, the Dv50 of the first negative electrode active material decreases when the grinding time is extended; and the Dv50 of the first negative electrode active material increases when the grinding time is shortened.
[0041] The present application has no particular limitation on the method for regulating D2 / D1, as long as the purpose of the present application can be achieved. For example, the value of D2 / D1 can be regulated by regulating the values of D2 and D1, and the regulation method is as described above.
[0042] The present application has no particular limitation on the method for regulating D2 / D3, as long as the purpose of the present application can be achieved. For example, the value of D2 / D3 can be regulated by regulating the respective values of D2 and D3, and the regulation method is as described above.
[0043] In one embodiment of the present application, the ionic conductivity of the fast ion conductor is 1.44×10 -5 S / m to 1.09×10 -3 S / m. Specifically, the ionic conductivity of the fast ion conductor can be 1.44×10 -5 S / m, 4×10 -5 S / m, 6×10 -5 S / m, 8×10 -5 S / m, 1×10 -4 S / m, 1.44×10 -4 S / m, 4×10 -4 S / m, 6×10 -4 S / m, 8×10 -4 S / m, 1×10 -3 S / m, 1.09×10 -3S / m may be a range consisting of any two of the above values. By regulating the ionic conductivity of the fast ion conductor within the scope of the present application, the conductivity of the negative electrode active material can be increased, which helps to further improve the cycle stability of the secondary battery.
[0044] In one embodiment of the present application, the fast ion conductor has a molecular formula of any one of formula (A), formula (B) or formula (C):
[0045] Li α M β La3Zr2O 12 (A)
[0046] In formula (A), M includes at least one of Ga, Al or Fe, satisfying: α+3β=7, α≥5.5, β≥0;
[0047] 7La γ R δ Zr2O 12 (B)
[0048] In formula (B), R is at least one of Ce or Y, satisfying: 3γ+3δ=9, γ≥2.5, δ≥0;
[0049] Li7La3Zr a X b Q c O 12 (C)
[0050] In formula (C), X and Q are each independently selected from at least one of Ta, Nb, Sn, Sb, W, Te, Cr or Y, satisfying: a+b+c=2, a≥1, b≥0, c≥0. In the present application, when the fast ion conductor is lithium lanthanum zirconium oxide and contains only four elements of Li, La, Zr and O, the fast ion conductor is an undoped fast ion conductor. When the fast ion conductor has the molecular formula of formula (A) and β is not equal to 0, the fast ion conductor is a Li-doped fast ion conductor; when the fast ion conductor has the molecular formula of formula (B) and δ is not equal to 0, the fast ion conductor is a La-doped fast ion conductor; when the fast ion conductor has the molecular formula of formula (C), b is not equal to 0 and c is not equal to 0, the fast ion conductor is a Zr-doped fast ion conductor. By selecting the above-mentioned Li-doped fast ion conductor, La-doped fast ion conductor or Zr-doped fast ion conductor, the electrochemical window of the undoped fast ion conductor can be expanded, and the electrochemical stability of the fast ion conductor can be increased, making it a more stable and efficient transition layer for conducting lithium ions, which is beneficial to further improve the cycle stability of the secondary battery.
[0051] In one embodiment of the present application, the fast ion conductor comprises Li7La3Zr2O12 , Li 6.28 Al 0.24 La3Zr2O 12 , Li 6.25 Ga 0.25 La3Zr2O 12 , Li 6.4 Ga 0.2 La3Zr2O 12 、Li7La 2.5 Ce 0.5 Zr2O 12 、Li7La 2.875 Y 0.125 Zr2O 12 or Li7La3ZrNb 0.5 Y 0.5 O 12 By selecting the above-mentioned fast ion conductor, a solid-state electrolyte membrane can be formed on the surface of the first negative electrode active material, which can provide a lithium ion diffusion channel and inhibit the side reaction between the first negative electrode active material and the electrolyte, protect the first negative electrode active material, improve the gas production of the secondary battery, and improve the cycle stability of the secondary battery.
[0052] In one embodiment of the present application, the negative electrode material layer also includes a binder and a conductive agent. Based on the total mass of the negative electrode material layer, the mass percentage of the negative electrode active material is 80% to 98%, the mass percentage of the fast ion conductor is 0.1% to 16%, and the sum of the mass percentages of the binder and the conductive agent is 1% to 4%. Among them, the mass percentage of the binder is 0.5% to 3%, and the mass percentage of the conductive agent is 0.5% to 1%. By regulating the mass percentage of the negative electrode active material and the fast ion conductor within the scope of the present application, the secondary battery has a higher energy density, and the fast ion conductor has an improved ability to protect the interface, thereby improving the gas production of the secondary battery and being able to improve the cycle stability of the secondary battery.
[0053] In the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer arranged on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be arranged on one surface of the negative electrode current collector along its own thickness direction, or it can be arranged on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the negative electrode current collector, as long as the purpose of this application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector, etc.
[0054] The present application has no particular restrictions on the binder, as long as the purpose of the present application can be achieved, for example, the binder may include but is not limited to polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene-butadiene rubber), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. The present application has no particular restrictions on the conductive agent, as long as the purpose of the present application can be achieved, for example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metal materials or conductive polymers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The conductive polymer may include, but is not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.
[0055] The present application has no particular restrictions on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 5μm to 12μm. The present application has no particular restrictions on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode material layer on one surface of the negative electrode current collector is 30μm to 250μm. The present application has no particular restrictions on the thickness of the negative electrode pole piece, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode pole piece is 50μm to 500μm.
[0056] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0057] In one embodiment of the present application, the negative electrode active material further includes a second negative electrode active material, the second negative electrode active material includes at least one of artificial graphite or natural graphite, and based on the total mass of the negative electrode active material, the mass percentage of the first negative electrode active material is 2% to 20%, preferably, the mass percentage of the first negative electrode active material is 6% to 13%, and the mass percentage of the second negative electrode active material is 80% to 98%. When the negative electrode active material further includes the second negative electrode active material, by regulating the mass percentage of the first negative electrode active material in the negative electrode active material within the scope of the present application, the secondary battery has a higher energy density, and the secondary battery has less expansion and improved cycle stability.
[0058] The second aspect of the present application provides a secondary battery, which includes the negative electrode sheet in any of the above embodiments. Therefore, the secondary battery provided by the present application is not easy to expand and has good cycle stability.
[0059] In the present application, the secondary battery also includes a positive electrode plate, which includes a positive electrode collector and a positive electrode material layer disposed on at least one surface of the positive electrode collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode collector along the thickness direction of itself, or it can be disposed on two surfaces of the positive electrode collector along the thickness direction of itself. It should be noted that the "surface" here can be the entire area of the positive electrode collector or a partial area of the positive electrode collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the positive electrode collector, as long as the purpose of this application can be achieved. For example, it can include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0060] The positive electrode material layer includes a positive electrode active material. The present application has no particular restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include lithium nickel cobalt manganese oxide (such as common NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganate, lithium iron manganese phosphate or lithium titanate. At least one of the positive electrode material layer also includes a positive electrode conductor and a positive electrode binder. The present application has no particular restrictions on the types of positive electrode conductors and positive electrode binders, as long as the purpose of the present application can be achieved. For example, the positive electrode binder can be at least one of the above-mentioned binders, and the positive electrode conductor can be at least one of the above-mentioned conductors. The present application has no particular restrictions on the mass ratio of the positive electrode active material, the positive electrode conductor, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0061] The present application has no particular restrictions on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode current collector is 5μm to 20μm. The present application has no particular restrictions on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode material layer on one surface of the positive electrode current collector is 30μm to 250μm. The present application has no particular restrictions on the thickness of the positive electrode sheet, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode sheet is 50μm to 500μm.
[0062] Optionally, the positive electrode plate may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0063] The secondary battery of the present application also includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent. The lithium salt may include various lithium salts commonly used in the art, such as at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the concentration of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned fluorinated carbonate compound may include but is not limited to at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0064] In the present application, the secondary battery also includes a separator to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of the separator may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0065] In the present application, the separator may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder for the diaphragm. The present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder for the diaphragm, for example, it may be at least one of the aforementioned binders. The polymer layer contains polymers, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).
[0066] The secondary battery of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.
[0067] In the present application, the secondary battery may include, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery, etc.
[0068] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging. Among them, the packaging bag is a packaging bag known in the art, and the present application does not limit this.
[0069] The third aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.
[0070] The present application does not particularly limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0071] Example
[0072] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0073] Test methods and equipment:
[0074] Particle size test:
[0075] The Dv50 of the first negative electrode active material and the Dv50 and Dv99 of the fast ion conductor were measured using a particle size analyzer (model: MasterSizer 2000).
[0076] Ionic conductivity test:
[0077] Different fast ion conductors were prepared into high-density ceramic sheets (density 0.96) by cold pressing, and gold was sprayed on both ends of the ceramic sheets to make blocking electrodes. The prepared blocking electrodes were subjected to AC impedance testing with a frequency range of 1MHz to 10Hz and a disturbance amplitude of 10mV. The ionic conductivity σ was calculated as follows: σ=d / Re×S.
[0078] Where d is the thickness of the sample under test (in cm); Re is the body impedance of the sample under test (in ohm), which can be obtained from the intersection of the semicircle arc and the oblique line in the Nyquist diagram of the electrochemical impedance spectroscopy; S is the effective area of the electrode (in cm 2 ).
[0079] Mechanical strength test of negative electrode:
[0080] Take the lithium-ion battery and disassemble it, separate the negative electrode sheet, and perform nanoindentation test on the negative electrode sheet. Press the rigid indenter (using the Bosch indenter) into the surface of the negative electrode sheet under the action of gradually increasing external force (the speed of external force increase is 200mN / min), and keep the load for 60s after the external force reaches the predetermined peak value (0.006N), and then remove the external force; during the loading-unloading process of the external force, use high-precision load-displacement testing technology to record the displacement of the rigid indenter and the load borne by the rigid indenter. The ratio of the load P borne by the rigid indenter when the external force reaches the peak value and is kept for 60s to the displacement h of the rigid indenter at this time is the elastic modulus E of the negative electrode sheet, that is, E=P / h.
[0081] Cycle performance test:
[0082] Place the lithium-ion battery in a 45°C constant temperature box, charge it to 4.3V at a constant current of 1C, charge it to 0.05C at a constant voltage at 4.3V, and then discharge it to 3V at a constant current of 4C. This is a charge and discharge cycle. Record the first discharge capacity as C1, and record the thickness of the lithium-ion battery in the first fully charged state as d1. Perform 300 charge and discharge cycles in the above manner, and record the discharge capacity after the 300th cycle as C. 300 , and the thickness in the fully charged state after the 300th cycle is recorded as d300. The above thicknesses are all tested using a panel pressure gap (PPG) thickness gauge (model: IEST PPG1000, Yuanneng Technology).
[0083] The cycle capacity retention rate of lithium-ion batteries = (C 300 / C1)×100%;
[0084] Thickness growth rate of lithium-ion battery = (d 300 -d1) / d1×100%.
[0085] Example 1-1
[0086] <Preparation of positive electrode sheet>
[0087] The positive electrode active material NCM ternary material (molecular formula LiNi 0.8 Co 0.1 Mn 0.1 O2), a positive electrode binder polyvinylidene fluoride (PVDF), and a positive electrode conductive agent conductive carbon black (Super P) are mixed, wherein the mass ratio of NCM, PVDF and Super P is 96:2:2, and a solvent N-methylpyrrolidone (NMP) is added, and the mixture is evenly mixed under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 75wt%; the positive electrode slurry is evenly coated on one side surface of a positive electrode collector aluminum foil with a thickness of 10μm, and dried at 90°C to obtain a positive electrode sheet with a single-sided positive electrode material layer coated with a coating thickness of 100μm, and the above steps are repeated on the other side surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer coated, and then cold pressed and cut to obtain a positive electrode sheet with a specification of 74mm×867mm.
[0088] <Preparation of negative electrode sheet>
[0089] The negative electrode active material, fast ion conductor Li7La3Zr2O 12 , sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), and carbon nanotubes (CNTs) are mixed in a mass ratio of 90:6.5:1:1.5:1, deionized water is added, and the mixture is uniformly mixed under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 45wt%. The negative electrode active material includes a first negative electrode active material, silicon dioxide SiO, and a second negative electrode active material, artificial graphite. Based on the total mass of the negative electrode active material, the mass percentage of the first negative electrode active material is 10%.
[0090] The negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil with a thickness of 10 μm, and dried at 90°C to obtain a negative electrode sheet with a single-sided negative electrode active material layer coated with a coating thickness of 100 μm. The above steps are repeated on the other side of the copper foil to obtain a negative electrode sheet with a double-sided negative electrode active material layer coated. After cold pressing and slitting, a negative electrode sheet with a specification of 78 mm × 875 mm is obtained.
[0091] <Preparation of Electrolyte>
[0092] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent. LiPF6 is dissolved in the above organic solvent, and vinylene carbonate is added and mixed to obtain an electrolyte. Based on the total mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, the mass percentage of vinylene carbonate is 3%, and the mass percentage of the organic solvent is 84.5%.
[0093] <Preparation of Separator Film>
[0094] A porous polypropylene film with a thickness of 14 μm was used.
[0095] <Preparation of lithium-ion batteries>
[0096] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in sequence, with the isolation film being placed between the positive electrode sheet and the negative electrode sheet to serve as an isolation. The electrode assembly is then wound into an electrode assembly, which is then placed in an aluminum-plastic film, and the electrolyte is injected and sealed. After standing, forming, and shaping, a lithium-ion battery is obtained.
[0097] Example 1-2 to Example 1-19
[0098] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0099] Example 2-1 to Example 2-6
[0100] Except that the relevant preparation parameters in <Preparation of Negative Electrode Sheet> are adjusted according to Table 2, the rest is the same as Example 1-3.
[0101] Example 3-1 to Example 3-3
[0102] Except that the relevant preparation parameters in <Preparation of Negative Electrode Sheet> are adjusted according to Table 3, the rest is the same as Example 1-3.
[0103] Example 4-1
[0104] Except for preparing the negative electrode sheet according to the following method, the rest is the same as Example 1-3.
[0105] <Preparation of negative electrode sheet>
[0106] The negative electrode active material, fast ion conductor Li7La3Zr2O 12, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), and carbon nanotubes (CNTs) are mixed in a mass ratio of 94.5:2:1:1.5:1, deionized water is added, and the mixture is evenly mixed under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 45%. The negative electrode active material includes a first negative electrode active material, silicon dioxide SiO, and a second negative electrode active material, artificial graphite. Based on the total mass of the negative electrode active material, the mass percentage of the first negative electrode active material is 2%.
[0107] The negative electrode slurry was evenly coated on one side of the negative electrode current collector copper foil with a thickness of 10 μm, and dried at 90°C to obtain a negative electrode sheet with a single-side negative electrode active material layer coated with a coating thickness of 100 μm, and then the above steps were repeated on the other side of the copper foil to obtain a negative electrode sheet with a double-side negative electrode active material layer coated, and then cold pressed and cut to obtain a negative electrode sheet with a specification of 78 mm × 875 mm. Among them, the mass percentage of the first negative electrode active material in the negative electrode active material is shown in Table 4.
[0108] Example 4-2 to Example 4-14
[0109] Except for adjusting the relevant preparation parameters according to Table 4 in <Preparation of Negative Electrode Sheet>, the rest is the same as Example 4-1.
[0110] Comparative Example 1-1
[0111] Except for preparing the negative electrode sheet according to the following method, the rest is the same as Example 1-1.
[0112] <Preparation of negative electrode sheet>
[0113] The negative electrode active material, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), and carbon nanotubes (CNTs) are mixed in a mass ratio of 96.5:1:1.5:1, deionized water is added, and the mixture is uniformly mixed under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 45%. The negative electrode active material includes a first negative electrode active material, silicon dioxide SiO, and a second negative electrode active material, artificial graphite. Based on the total mass of the negative electrode active material, the mass percentage of the first negative electrode active material is 10%.
[0114] The negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil with a thickness of 10 μm, and dried at 90°C to obtain a negative electrode sheet with a single-sided negative electrode active material layer coated with a coating thickness of 100 μm. The above steps are repeated on the other side of the copper foil to obtain a negative electrode sheet with a double-sided negative electrode active material layer coated. After cold pressing and slitting, a negative electrode sheet with a specification of 78 mm × 875 mm is obtained.
[0115] Comparative Example 1-2 to Comparative Example 1-5
[0116] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0117] Comparative Example 4-1
[0118] Except for preparing the negative electrode sheet according to the following method, the rest is the same as Example 1-1.
[0119] <Preparation of negative electrode sheet>
[0120] The negative electrode active material, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), and carbon nanotubes (CNTs) are mixed in a mass ratio of 96.5:1:1.5:1, deionized water is added, and the mixture is uniformly mixed under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 45%. The negative electrode active material includes a first negative electrode active material, silicon dioxide SiO, and a second negative electrode active material, artificial graphite. Based on the total mass of the negative electrode active material, the mass percentage of the first negative electrode active material is 6%.
[0121] The negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil with a thickness of 10 μm, and dried at 90°C to obtain a negative electrode sheet with a single-sided negative electrode active material layer coated with a coating thickness of 100 μm. The above steps are repeated on the other side of the copper foil to obtain a negative electrode sheet with a double-sided negative electrode active material layer coated. After cold pressing and slitting, a negative electrode sheet with a specification of 78 mm × 875 mm is obtained.
[0122] Comparative Example 4-2
[0123] Except that the relevant preparation parameters in <Preparation of Negative Electrode Sheet> are adjusted according to Table 4, the rest is the same as Comparative Example 4-1.
[0124] Comparative Example 4-3
[0125] Except for preparing the negative electrode sheet according to the following method, the rest is the same as Example 4-1.
[0126] <Preparation of negative electrode sheet>
[0127] The negative electrode active material (including only the second negative electrode active material artificial graphite), the fast ion conductor Li7La3Zr2O 12, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), and carbon nanotubes (CNTs) are mixed in a mass ratio of 94.5:2:1:1.5:1, deionized water is added, and the mixture is evenly mixed under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 45%; the negative electrode slurry is evenly coated on one side of a negative electrode current collector copper foil with a thickness of 10 μm, and dried at 90°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode active material layer with a coating thickness of 100 μm, and the above steps are repeated on the other side of the copper foil to obtain a negative electrode sheet with a double-sided coating of a negative electrode active material layer, and then cold pressed and cut to obtain a negative electrode sheet with a specification of 78 mm×875 mm.
[0128] The preparation parameters and electrical performance parameters of each embodiment and comparative example are shown in Tables 1 to 4.
[0129] Table 1
[0130]
[0131]
[0132] Note: In Table 1, “ / ” indicates no relevant preparation parameters.
[0133] Referring to Table 1, it can be seen from Examples 1-1 to 1-19 and Comparative Examples 1-1 to 1-5 that when the types of the first negative electrode active material and the fast ion conductor, at least part of the fast ion conductor is disposed on the surface of the first negative electrode active material, and the values of D2 / D1 and D2 are within the scope of this application, the negative electrode sheet has a higher elastic modulus, and the lithium ion battery has a higher capacity retention rate and a lower thickness expansion rate, which indicates that the negative electrode sheet has better mechanical properties and the lithium ion battery has better cycle stability. It can be seen from Examples 1-1 to 1-5 that the Dv50 and Dv99 of the fast ion conductor gradually increase, and the elastic modulus of the negative electrode sheet gradually decreases. This is because when the particle size of the fast ion conductor is small, it can be effectively distributed on the surface of the negative electrode active material, participate in the film formation of the solid-state electrolyte membrane, enhance the cohesive force, and make the elastic modulus of the negative electrode sheet larger and the mechanical properties of the negative electrode sheet better.
[0134] In Comparative Examples 1-1 to 1-5, the elastic modulus of the negative electrode plate is low, the capacity retention rate of the lithium-ion battery is low, and the thickness expansion rate is high, indicating that the mechanical properties of the negative electrode plate are poor and the cycle stability of the lithium-ion battery is poor.
[0135] The Dv50 (i.e., D1) of the first negative electrode active material also generally affects the expansion and cycle stability of the lithium-ion battery. It can be seen from Examples 1-3, 1-6 to 1-8, 1-17, and 1-18 that by adjusting the value of D1 within the scope of this application, the negative electrode sheet has a higher elastic modulus, and the lithium-ion battery has a higher capacity retention rate and a lower thickness expansion rate, which indicates that the negative electrode sheet has better mechanical properties and the lithium-ion battery has better cycle stability.
[0136] The ratio D2 / D3 of the Dv50 of the fast ion conductor to the Dv99 of the fast ion conductor will also generally affect the expansion and cycle stability of the lithium ion battery. It can be seen from Examples 1-3, 1-9 to 1-12, and 1-19 that by adjusting the value of D2 / D3 within the scope of this application, the negative electrode sheet has a higher elastic modulus, and the lithium ion battery has a higher capacity retention rate and a lower thickness expansion rate, which indicates that the negative electrode sheet has better mechanical properties and the lithium ion battery has better cycle stability.
[0137] The Dv99 (i.e., D3) of the fast ion conductor will also generally affect the expansion and cycle stability of the lithium-ion battery. It can be seen from Examples 1-2, 1-13 to 1-15 that by adjusting the value of D3 within the scope of this application, the negative electrode sheet has a higher elastic modulus, and the lithium-ion battery has a higher capacity retention rate and a lower thickness expansion rate, which indicates that the negative electrode sheet has better mechanical properties and the lithium-ion battery has better cycle stability.
[0138] Depend on Figure 2 It can be seen that in the negative electrode sheet of Example 1-1, the fast ion conductor (white particles with smaller particle size) is distributed on the surface of the first negative electrode active material silicon dioxide SiO (white particles with larger particle size).
[0139] Table 2
[0140]
[0141] The type and ion conductivity of the fast ion conductor usually also affect the expansion and cycle stability of the lithium-ion battery. From Examples 2-1 to 2-6, it can be seen that when lithium lanthanum zirconium oxide doped with different elements is selected, its ion conductivity is different, the negative electrode plate has a higher elastic modulus, and the lithium-ion battery has a higher capacity retention rate and a lower thickness expansion rate, which means that the negative electrode plate has better mechanical properties and the lithium-ion battery has better cycle stability.
[0142] Table 3
[0143]
[0144]
[0145] When the negative electrode active material includes a first negative electrode active material and a second negative electrode active material, the mass percentage of the negative electrode active material and the fast ion conductor usually affects the expansion, cycle stability and energy density of the lithium ion battery. It can be seen from Examples 1-3 and 3-1 to 3-3 that by adjusting the mass percentage of the negative electrode active material and the fast ion conductor within the scope of this application, the negative electrode plate has a higher elastic modulus, and the lithium ion battery has a higher capacity retention rate and a lower thickness expansion rate, which indicates that the negative electrode plate has better mechanical properties and the lithium ion battery has better cycle stability.
[0146] Table 4
[0147]
[0148]
[0149] Note: In Table 4, “ / ” indicates no relevant preparation parameters.
[0150] When the negative electrode active material includes a first negative electrode active material and a second negative electrode active material, the mass percentage of the first negative electrode active material in the negative electrode active material usually affects the expansion, cycle stability and energy density of the lithium-ion battery. It can be seen from Examples 4-1 to 4-14 that when the negative electrode active material also includes a second negative electrode active material, by adjusting the mass percentage of the first negative electrode active material in the negative electrode active material within the scope of this application, the negative electrode sheet has a higher elastic modulus, and the lithium-ion battery has a higher capacity retention rate and a lower thickness expansion rate, which indicates that the negative electrode sheet has better mechanical properties and the lithium-ion battery has better cycle stability. It can be seen from Comparative Examples 4-1 to Comparative Examples 4-2 that when the negative electrode active material includes a first negative electrode active material and a second negative electrode active material, and the negative electrode material layer does not include a fast ion conductor, the elastic modulus of the negative electrode sheet is lower, the capacity retention rate of the lithium-ion battery is lower, and the thickness expansion rate is higher, indicating that the mechanical properties of the negative electrode sheet are poor and the cycle stability of the lithium-ion battery is poor.
[0151] It can be seen from Example 4-1 to Example 4-4 that when the mass percentage of the negative electrode active material (including silicon oxide and artificial graphite) remains unchanged and the mass percentage of silicon oxide in the negative electrode active material increases, the elastic modulus of the negative electrode plate increases. This is because the mechanical strength of silicon oxide is higher and the mechanical strength of artificial graphite is lower. As the silicon oxide content increases, the mechanical strength of the negative electrode plate increases.
[0152] It can be seen from Examples 4-5 to 4-9 that when the mass percentage of the first negative electrode active material in the negative electrode active material remains unchanged (6%) and the mass percentage of the negative electrode active material gradually decreases, the mass percentage of the fast ion conductor gradually increases, the elastic modulus of the negative electrode plate gradually increases, the capacity retention rate of the lithium ion battery gradually increases, and the thickness expansion rate gradually decreases. However, when the mass percentage of the negative electrode active material is 76.5%, due to the low mass percentage of the negative electrode active material, the energy density of the lithium ion battery will be lower.
[0153] It can be seen from Examples 4-10 to 4-14 that when the mass percentage of the first negative electrode active material in the negative electrode active material remains unchanged (13%) and the mass percentage of the negative electrode active material gradually decreases, the mass percentage of the fast ion conductor gradually increases, the elastic modulus of the negative electrode plate gradually increases, the capacity retention rate of the lithium ion battery gradually increases, and the thickness expansion rate gradually decreases. However, when the mass percentage of the negative electrode active material is 76.5%, due to the low mass percentage of the negative electrode active material, the energy density of the lithium ion battery will be lower.
[0154] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0155] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0156] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material and a fast ion conductor, wherein the negative electrode active material comprises a first negative electrode active material, at least part of the fast ion conductor is disposed on the surface of the first negative electrode active material, the first negative electrode active material comprises at least one of silicon oxide or silicon carbide, and the fast ion conductor is lithium lanthanum zirconium oxide; The Dv50 of the first negative electrode active material is D1 μm, the Dv50 of the fast ion conductor is D2 μm, D2 / D1≤0.2, and 0.05≤D2≤1.
2. The negative electrode sheet according to claim 1, wherein: 0.01≤D2 / D1≤0.
14.
3. The negative electrode sheet according to claim 1, wherein: 0.3≤D2≤0.7。 4. The negative electrode sheet according to claim 1, wherein: 5≤D1≤15。 5. The negative electrode sheet according to claim 1, wherein: The Dv99 of the fast ion conductor is D3 μm, 0.1≤D2 / D3<1.
6. The negative electrode sheet according to claim 5, wherein: 0.5≤D2 / D3<1.
7. The negative electrode sheet according to claim 5, wherein: 0.5≤D3≤5。 8. The negative electrode sheet according to claim 1, wherein: The ionic conductivity of the fast ion conductor is 1.44×10 - 5 S / m to 1.09×10 -3 S / m.
9. The negative electrode sheet according to claim 1, wherein: The fast ion conductor has a molecular formula of any one of formula (A), formula (B) or formula (C): <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> α <h2 style=";text-align:left;direction:ltr"> M<h2 style=";text-align:left;direction:ltr"> β <h2 style=";text-align:left;direction:ltr"> La3Zr2O<h2 style=";text-align:left;direction:ltr"> 12 <h2 style=";text-align:left;direction:ltr"> (A) In formula (A), M includes at least one of Ga, Al or Fe, satisfying: α+3β=7, α≥5.5, β≥0; Li7La γ R δ Zr2O 12 (B) In formula (B), R is at least one of Ce or Y, satisfying: 3γ+3δ=9, γ≥2.5, δ≥0; Li7La3Zr a X b Q c O 12 (C) In formula (C), X and Q are each independently selected from at least one of Ta, Nb, Sn, Sb, W, Te, Cr or Y, satisfying: a+b+c=2, a≥1, b≥0, c≥0.
10. The negative electrode sheet according to claim 9, wherein: The fast ion conductor includes Li7La3Zr2O 12 , Li 6.28 Al 0.24 La3Zr2O 12 , Li 6.25 Ga 0.25 La3Zr2O 12 , Li 6.4 Ga 0.2 La3Zr2O 12 、Li7La 2.5 Ce 0.5 Zr2O 12 、Li7La 2.875 Y 0.125 Zr2O 12 or Li7La3ZrNb 0.5 Y 0.5 O 12 At least one of .
11. The negative electrode sheet according to claim 1, wherein: The negative electrode material layer also includes a binder and a conductive agent. Based on the total mass of the negative electrode material layer, the mass percentage of the negative electrode active material is 80% to 98%, the mass percentage of the fast ion conductor is 0.1% to 16%, and the sum of the mass percentages of the binder and the conductive agent is 1% to 4%.
12. The negative electrode sheet according to claim 11, wherein: The negative electrode active material further includes a second negative electrode active material, which includes at least one of artificial graphite or natural graphite. Based on the total mass of the negative electrode active material, the mass percentage of the first negative electrode active material is 2% to 20%. 13 . A secondary battery comprising the negative electrode sheet according to claim 1 . 14 . An electronic device comprising the secondary battery according to claim 13 .